Digital Waqf Ecosystems and the Institutional Coordination of Climate Finance - Hazik Mohamed (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2026)
Climate finance plays a critical role in supporting the transition to a low-carbon, climate-resilient economy. However, persistent financing gaps, fragmented governance, and limited institutional coordination continue to constrain the mobilization and effective allocation of resources for climate mitigation and adaptation. Islamic social finance, particularly waqf, has attracted growing attention as a complementary mechanism for promoting sustainable development. This study proposes a Digital Waqf Ecosystem (DWE), an integrated conceptual framework linking waqf institutions, digital governance, and climate finance to enhance transparency, accountability, and institutional coordination. The study adopts a conceptual research design, synthesizing literature on climate finance, Islamic social finance, digital governance, and institutional theory to develop the proposed framework. To examine its internal consistency under uncertainty, the study employs Monte Carlo simulation as an exploratory technique, evaluating interactions among digital governance, institutional trust, ethical capital mobilization, catalytic climate finance, and climate impact efficiency across alternative governance scenarios. The simulation results suggest that stronger digital governance improves institutional trust, mobilizes ethical capital, enhances integration with climate finance mechanisms, and produces consistent climate impact outcomes. While exploratory rather than predictive, the findings demonstrate the potential of digitally governed waqf institutions to strengthen institutional coordination within sustainable finance ecosystems. The study contributes to the literature by developing an integrated institutional framework that connects Islamic social finance, digital governance, and climate finance within a unified governance architecture. The findings offer practical insights for policymakers, waqf institutions, Islamic financial institutions, and development organizations seeking to strengthen governance and improve the effectiveness of climate finance initiatives.